“Sevgilerde” şiiri üzerine bir tahlil denemesi - Şahin, Veysel (My University, 2006)
İnsanlar tarafından hissedilen sevgi, gizliliklerle dolu, eylemsel bir olgudur. İnsan sevgi edimini, kalbinde ve bilinçaltında büyütür. Dünya hızlı bir şekilde değişerek metalaşıyor. Bu yüzden insan, sırlarla dolu sevgi edimini bilinçaltında yaşatmak zorunda kalıyor. Biz bu çalışmamızda, sevgilerin neden yarınlara ertelendiğini ve insanların bu macerasal düşü gerçekleştirme serüvenlerini açıklamaya çalıştık.

The love felt by human beings is full of secrets and is a functional phenomena. The human grows the love up in his/her heart and conscious. The world changes fast and is materialized and so, the human has to make live this phenomena which is full of secrets in the conscious. In thiss study, we tried to explain why the love is postponed to the future and the adventueres of the people to make true that adventurous dream. Key Words: Behçet Necatigil, love, loves, timidty, seizing.
An experimental analysis on the poem “Sevgilerde”
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Behçet Necatigil; Sevgi; Sevgiler; Çekingenlik; Tutukluk